Terrestrial laser scanning data of the Nesslrinna landslide close to Obergurgl, Austria acquired during the Innsbruck Summer School of Alpine Research [dataset] - Pfeiffer, Jan; Wujanz, Daniel; Zieher, Thomas; Rutzinger, Martin; Scaioni, Marco; Höfle, Bernhard; Lindenbergh, Roderik; Oude Elberink, Sander; Pirotti, Francesco; Bremer, Magnus; Hämmerle, Martin (PANGAEA - Data Publisher for Earth & Environmental Science, 2019)
Terrestrial laser scanning (TLS) allows one to acquire point clouds representing the surface at a certain time (epoch). Acquiring at least two point clouds at two different epochs enables the detection of surface changes caused by certain environmental processes. This data publication contains point clouds representing the surface of the "Nesslrinna" landslide and its surrounding located on an eastern slope between Zwieselstein and Obergurgl right below the Timmelsjoch toll station. Point clouds were acquired during the Innsbruck Summer School of Alpine Research "Close Range Sensing Techniques in Alpine Terrain" using different TLS sensors. Comparing different epochs enables the detection of surface changes that have occurred due to landslide activity between each acquisition date.